Self-efficacy and self-care of a working mother-student during COVID-19 pandemic - Tan, Choe Chai; Zakaria, Noor Syamilah (Human Resource Management Academic Research Society, 2021)
Nobody expected the COVID-19 pandemic which has affected every facet of our lives. The focus of this paper is to explore the impact of the COVID-19 pandemic on the mental health of the working mother-student. Hence, the need to evaluate and understand how the self-efficacy practices of working mother- student has changed during the pandemic. The methodology used is the narration of personal reflection of a mother’s experience in taking care of her husband, a COVID-19 patient, while pursuing her PhD during the peak of the pandemic in Malaysia. The findings of the study are elaborated in this paper. The study focuses on the details and challenges of the quarantine period and the techniques to overcome these challenges, such as mastery experiences, social persuasion, physiological and emotional states. Through personal narratives, common adverse psychological consequences of quarantine were identified. Self-acceptance, self-compassion, and self-care were elaborated to enhance self-efficacy during and beyond the pandemic.